KEBIJAKAN PEMERINTAH MENDUKUNG PENINGKATAN USAHA SAPI POTONG DI PETERNAK - Rusdiana, Supardi; Talib, Chalid (SOCA: Jurnal Sosial Ekonomi Pertanian, 2019)
Government policy to develop beef cattle in breeders, the aim of which is to be able to meet the needs of food originating from meat and increase farmers' income.The purpose of this paper is to review the implementation and empirically to find out the Government's policy in supporting the improvement of beef cattle business in farmers. The beef cattle business in farms with various daily body weight gain (PBBH) arranged at a 5% level of confidence was very significant (P>0.05). The advantage of IB cattle breeders from IB yields is IDR.4.575.000/year and B/C value of 1,2. The beef cattle business by grazing the plantation area and rubber farmers' profits is IDR.3.185.000/year B/C of 1.2. The business of beef cattle by means of breeding and fattening is still a lot of effort, so that it needs government support and policy so that farmers can continue to maintain their business. Efforts to develop animal husbandry must be supported by market opportunities. In addition to improving technology, infrastructure improvements, capability and progress of farmers can be managed by managing livestock business. Through Government support and policy, it is expected that an increase in beef cattle population and the economic value of farmers will increase.